The Role of Cytokinin Homeostasis in the Regulation of PIN7 - Albalawi, Khulud (2023)
Phytohormones regulate virtually every aspect of plant growth and development. The interaction between auxin and cytokinin determines the vascular pattern in the root. One key node of crosstalk between these hormones, involves cytokinin promoting the transcription of the auxin efflux transporter PIN-FORMED 7 (PIN7). However, the mechanism by which this occurs is not known. A forward genetic screen to identify novel loci regulating PIN7::PIN7:GFP in the root identified a number of mutants. One of them, in a mutant called 56B2, is in the promoter of the CYTOKININ OXIDASE/DEHYDROGENASE 5 (CKX5) gene. In this project the phenotype of this mutant was characterised in detail. It has been shown that in addition to mis-expression of PIN7 in the root tip, this mutant also shows reduced sensitivity to cytokinin and defects in organ formation in both lateral roots and leaves. It was demonstrated that CKX5 is expressed in the root vascular cylinder, lateral root primordia, and the shoot apical meristem. These are all regions consistent with the phenotypes that was observed in 56B2. To test whether the mutation in the CKX5 promoter causes mis-expression of CKX5 in root tips, reporter lines were developed for CKX5 with either wild-type or 56B2-like promoters. Surprisingly, these showed no difference in CKX5 levels in the root meristem. Then variation in natural accessions has been looking and two closely related lines (Kardz 1 and 2) that differ from each other with exactly the same substitution present in 56B2 were identified. It has been shown that several of the phenotypes present in 56B2 are shared with Kardz-2, but that CKX5 levels are not altered in the root tip. As cytokinin is known to be transported from shoots to root via the phloem, the results are consistent with a hypothesis in which cell non-autonomous regulation of CKX5 causes the root phenotype shown in 56B2. A series of experiments were presented that could explore this further.